Comparative In vitro Evaluation of Different Brands of 40 mg Furosemide Tablets - Darine Abozaid; Wedad Masoud; Azah Manbi (AlQalam Journal of Medical and Applied Sciences, 2025)
Concerns about medication failure and the high rates of morbidity and mortality linked to the distribution and use of fake, counterfeit, and inferior medications are major concerns for patients, healthcare providers, and drug regulatory agencies. To provide the intended therapeutic effect, a medication must include the appropriate quantity of the active pharmacological ingredient in addition to the necessary physical properties. One popular and effective diuretic medication that is mostly used to treat oedema and hypertension is furosemide. The market today offers a wide variety of furosemide formulations intended for oral consumption. The purpose of this study is to examine a number of Furosemide tablet brands sold in Al Bayda, Libya, to confirm that they comply with the regulatory requirements specified by the US Pharmacopoeia and the British Pharmacopoeia as well as label claims. Furosemide tablets of six different brands were chosen at random from several local pharmacies in Al Bayda, Libya. In addition to other significant evaluation criteria like weight variation, hardness, friability, disintegration time, dissolution test, and drug content assay, the samples’ visual qualities were also analyzed. The findings verified that all brands were deemed to be of good quality and met the requirements of the official Pharmacopoeias. Additionally, they had dissolution profiles that were comparable to the innovator’s, enabling their interchangeability.